need to simplify

(-2p)^{4} is same as: (-2p)(-2p)(-2p)(-2p) --> (-2)^{4 }*p^{4
}--->**16p**^{4}

need to simplify

Tutors, please sign in to answer this question.

(-2p)^{4} is same as: (-2p)(-2p)(-2p)(-2p) --> (-2)^{4 }*p^{4
}--->**16p**^{4}

You have a multiplication, raised to a power.

So, there's a theory that says:

(a*b)^c = (a^c)*(b^c)

- this can be proven by expanding and rearranging the order of the multiplications. As an example:

(2*3)^4 = (2*3)*(2*3)*(2*3)*(2*3) = (2*2*2*2)*(3*3*3*3) = (2^4)*(3^4) = 16*81...

Further, if you do not have a value for your variable, then you can't compute a simpler expression that combines the variable with the power - once you get down to p^4, that's as simple as that part of the expression will get.